Understanding the patient voice in gout: a quantitative study conducted in Europe. Issue 1 (April 2020) - Meulemeester, Marc De; Mateus, Elsa; Wieberneit-Tolman, Hilda; Betteridge, Neil; Ireland, Lucy; Petersen, Gudula; Maske, Nina Jeanette; Jansen, Tim L; Perez-Ruiz, Fernando
No abstract available